Pemetaan Tingkat Kemampuan Kompetensi Membaca Al-Qur’an Umat Islam Di Kota Kendari - Sukring Sukring (Universitas Islam Negeri Fatmawati Sukarno Bengkulu, 2020)
Abstract: Mapping of Competency Levels of Reading Al-Qur'an Muslims in Kendari CityAl-Qur'an is a revelation from Allah Almighty, revealed as a guide for human life, contains various aspects of human life since it was revealed to the end of time, reading the Koran is rewarded, opens the door of Grace, becomes medicine (syifaa) for both the physical and the soul , provide inspiration, open the realm of human thought, and as a source of knowledge. With the development of science and technology, it is a challenge for Muslims, especially in the city of Kendari, in terms of the desire and concern of the Muslim community to read the Qur'an, in this study the authors found the factors inhibiting the Muslim community in Kendari City in the medium and low categories in reading the Koran, among others; More interested in playing Gadgets in their spare time ”with an average of 0.62. Then the next highest is on the indicator “Too many tasks or jobs at home or work” with an average of 0.51. And the third lowest indicator is